PENGARUH INDEKS PEMBANGUNAN MANUSIA DAN LAJU PERTUMBUHAN EKONOMI TERHADAP TINGKAT PENGANGGURAN TERBUKA DI KOTA MEDAN TAHUN 2003-2024 - Tanjung, Adetia Azmi; Affiah, Hajar; Syera, Inda Arfa (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: The purpose of this study is to determine the effect of the Human Development Index and the Economic Growth Rate on the Open Unemployment Rate in Medan City from 2003 to 2024. The data used in this study is time series data for the period 2003-2024 sourced from the Central Statistics Agency (BPS) of Medan City. This study uses multiple linear analysis with the Ordinary Least Square (OLS) model processed with the eviews data processing tool. The results of the t-test research on eviews data processing, the probability of the Human Development Index is 0.0000. Where 0.0000 <0.05 so it is concluded that the Human Development Index has a significant effect on the Open Unemployment Rate. Then the variable Economic Growth Rate obtained a probability value of 0.0825. Where 0.0825> 0.05 so it can be concluded that the Economic Growth Rate does not have a partial effect on the Open Unemployment Rate. Then finally the f test was carried out. Where the probability value of the f statistic was 0.000001. This means that the Human Development Index and Economic Growth Rate have a simultaneous effect on the Open Unemployment Rate in Medan City. Keywords: Human Development Index, Economic Growth Rate, Open Unemployment Rate Abstrak: Tujuan penelitian ini untuk mengetahui pengaruh Indeks Pembangunan Manusia dan Laju Pertumbuhan Ekonomi terhadap Tingkat Pengangguran Terbuka di Kota Medan tahun 2003 sampai dengan tahun 2024. Data yang digunakan dalam penelitian ini adalah data time series dalam kurun waktu 2003-2024 yang bersumber dari Badan Pusat Statistik (BPS) Kota Medan. Penelitian ini menggunakan analisis linear berganda dengan model Ordinary Least Square (OLS) yang diolah dengan alat bantu olah data eviews. Hasil penelitian uji t pada olah data eviews, probabilitas Indeks Pembangunan Manusia sebesar 0.0000. Dimana 0.0000 < 0,05 sehingga disimpulkan Indeks Pembangunan Manusia berpengaruh signifikan terhadap Tingkat Pengangguran Terbuka. Kemudian variabel Laju Pertumbuhan Ekonomi diperoleh nilai probabilitas 0.0825. Dimana 0.0825 > 0.05 sehingga dapat disimpulkan bahwa Laju Pertumbuhan Ekonomi tidak berpengaruh secara parsial terhadap Tingkat Pengangguran Terbuka. Kemudian terakhir dilakukan uji f. Dimana nilai prob f statistiknya 0.000001. Artinya Indeks Pembangunan Manusia dan Laju Pertumbuhan Ekonomi berpengaruh secara simultan terhadap Tingkat Pengangguran Terbuka di Kota Medan.  Kata kunci: Indeks Pembangunan Manusia, Laju Pertumbuhan Ekonomi, Tingkat Pengangguran Terbuka